Eight‐color immunophenotyping of T‐, B‐, and NK‐cell subpopulations for characterization of chronic immunodeficiencies. Issue 3 (31st January 2014) - Boldt, Andreas; Borte, Stephan; Fricke, Stephan; Kentouche, Karim; Emmrich, Frank; Borte, Michael; Kahlenberg, Franka; Sack, Ulrich
<x xml:space="preserve">Abstract</x> Background The heterogeneity of primary and secondary immunodeficiencies demands for the development of a comprehensive flow cytometric screening system, based on reference values that support a standardized immunophenotypic characterization of most lymphocyte subpopulations. Methods Peripheral blood samples from healthy adult volunteers (n = 25) were collected and split into eight panel fractions (100 µl each). Subsequently, premixed eight‐color antibody cocktails were incubated per specific panel of whole blood to detect and differentiate cell subsets of: (i) a general lymphocyte overviews, (ii) B‐cell subpopulations, (iii) CD4+ subpopulations, (iv) CD8+ subpopulations, (v) regulatory T‐cells, (vi) recent thymic emigrants (RTE), (vii) NK‐cell subpopulations, and (viii) NK‐cell activation markers. All samples were lysed, washed, and measured by flow cytometry. FACS DIVA software was used for data analysis and calculation of quadrant statistics (mean values, standard error of mean, and percentile ranges). Results Whole blood staining of lymphocytes provided the analysis of: (i) CD3+, 4+, 8+, 19+, 16/56+, and activated CD4/8 cells; (ii) immature, naïve, nonswitched/switched, memory, (activated) CD21low, transitional B‐cells, plasmablasts/plasmacells; (iii and iv) naïve, central memory, effector, effector memory, TH1/TH2/TH17‐like, and CCR5+CD8‐cells; (v) CD25+, regulatory T‐cells (naïve/memory, HLA‐DR+); (vi) α/β‐ and γ/δ‐T‐cells, RTE in CD4/CD8 cells; (vii) immature/mature CD56bright, CD94/NKG2D+ NK‐cells; and (viii) Nkp30, 44, 46, and CD57+NK‐cells. Clinical examples and quadrant statistics are provided. Conclusion The present study represents a practical approach to standardize the immunophenotyping of most T‐, B‐, and NK‐cell subpopulations. That allows differentiating whether abnormalities or developmental shifts observed in lymphocyte subpopulations originates either from primary or secondary immunological disturbance. © 2014 International Clinical Cytometry Society